Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Dan Pemahaman Konsep Belajar Siswa Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII Di UPTD SMP Negeri 5 Pematangsiantar Tahun Ajaran 2023/2024 - Casida Paramida Br Sinaga; Benjamin Albert Simamora (Journal on Education, 2024)
This research aims to determine whether there is an influence of the Jigsaw Type Cooperative learning model and understanding of Jigsaw student learning concepts on student learning outcomes in social studies subjects in class VIII at UPTD SMP Negeri 5 Pematangsiantar for the 2023/2024 academic year. The results of this research show that the variables of the jigsaw type cooperative learning model have an influence on student learning outcomes. Where the t-count value of the jigsaw type cooperative learning model variable (X1) is 2.983 > ttable 2.000 and the significance value is 0.004 < 0.05. So it can be concluded that Ha1 is accepted. The variable understanding students' learning concepts influences student learning outcomes. Where the t value of the variable understanding students' learning concepts (X2) is 2.055 > t table 2.000 and the significance value is 0.044 < 0.05. So it can be concluded that Ha2 is accepted. For the F test results (simultaneous), the Fcount value was 5.161 > Ftable 3.15. So it can be concluded simultaneously that the variables of the jigsaw type cooperative learning model and students' understanding of learning concepts influence student learning outcomes. From these results it can be seen that Ha3 is accepted.